2022
DOI: 10.1177/10949968221074726
|View full text |Cite
|
Sign up to set email alerts
|

The Unanticipated Dynamics of Promoting Crowdfunding Donation Campaigns on Social Media

Abstract: Crowdfunding is an online method of fundraising from a large audience. Digital Word of Mouth (DWOM) via social media has become a popular promotion platform for crowdfunding campaigns due to its negligible nominal cost. While one may expect that promoting these campaigns on social media may steadily increase donations, the exact dynamics of such promotions have not been studied for donation-based crowdfunding. We collect panel data on several unique donation campaigns from a major donation-based crowdfunding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The network impact is more present at the beginning and end of a campaign (Borst et al, 2018) since early contributions of “family and friends” are later replaced by loyal backers who care more about the content of the project than the creator (Skirnevskiy et al, 2017). This connects to the finding that social media is most effective at a campaign's beginning (Dehdashti et al, 2022), since with soliciting close ties, social media platforms play an essential role, with Facebook being the leading media platform from the start (Hekman & Brussee, 2013; Hong et al, 2015), and to this day (Van Teunenbroek & Hasanefendic, 2022). Researchers explain that Twitter focuses on objective information and quality signals, while Facebook focuses on supporting connections and social norms.…”
Section: Crowdfunding Features and Mechanisms Impacting Giving Behaviormentioning
confidence: 81%
See 1 more Smart Citation
“…The network impact is more present at the beginning and end of a campaign (Borst et al, 2018) since early contributions of “family and friends” are later replaced by loyal backers who care more about the content of the project than the creator (Skirnevskiy et al, 2017). This connects to the finding that social media is most effective at a campaign's beginning (Dehdashti et al, 2022), since with soliciting close ties, social media platforms play an essential role, with Facebook being the leading media platform from the start (Hekman & Brussee, 2013; Hong et al, 2015), and to this day (Van Teunenbroek & Hasanefendic, 2022). Researchers explain that Twitter focuses on objective information and quality signals, while Facebook focuses on supporting connections and social norms.…”
Section: Crowdfunding Features and Mechanisms Impacting Giving Behaviormentioning
confidence: 81%
“…The network impact is more present at the beginning and end of a campaign (Borst et al, 2018) since early contributions of "family and friends" are later replaced by loyal backers who care more about the content of the project than the creator (Skirnevskiy et al, 2017). This connects to the finding that social media is most effective at a campaign's beginning (Dehdashti et al, 2022) creator is important (Cicchiello et al, 2022) and often happens within the platform via comments and updates.…”
Section: Main Themesmentioning
confidence: 99%
“…This highlights a key methodological contribution this study, considering that the majority of the existing research studied crowdfunding via data scraping (Nielsen & Binder, 2021; Polzin et al, 2018), often focusing on data from the Kickstarter platform (Kunz et al, 2016). In addition, earlier studies focused primarily on one platform at a time (e.g., André et al, 2017; Dehdashti et al, 2022; Gleasure & Feller, 2016; Greenberg & Mollick, 2015; Kim et al, 2022), even though the difference between crowdfunding platforms is substantial (Belleflamme et al, 2015). We make up for this by including a large sample of random individuals not connected to a platform.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our research also contributes to the literature concerning herding behavior. Previous research indicates that the herding effect is also observed in cases of charity, in which individuals tend to follow others' behavior (Dehdashti et al, 2022), especially those exhibited by their friends (Bekkers & Wiepking, 2011;Meer, 2011).…”
Section: Theoretical Contributionsmentioning
confidence: 97%